Comparative transcriptomic profiling of peach and nectarine cultivars reveals cultivar-specific responses to chilled postharvest storage - Muto, Antonella; Bruno, Leonardo; Madeo, Maria Letizia; Ludlow, Richard; Ferrari, Michele; Stimpson, Louise; LoGiudice, Claudio; Picardi, Ernesto; Ferrante, Antonio; Pasti, Luisa; Müller, Carsten T.; Chiappetta, Adriana Ada Ceverista; et al. (Frontiers in Plant Science, 2022)
Peach (Prunus persica (L.) Batsch,) and nectarine fruits (Prunus persica (L.) Batsch, var nectarine), are characterized by a rapid deterioration at room temperature. Therefore, cold storage is widely used to delay fruit post-harvest ripening and extend fruit commercial life. Physiological disorders, collectively known as chilling injury, can develop typically after 3 weeks of low-temperature storage and affect fruit quality. Here, we performed a comparative transcriptomic analysis to identify regulatory pathways that develop before chilling injury symptoms are detectable. Next generation sequencing on the fruits of one peach and one nectarine cultivar, Sagittaria and Big Top, respectively), over 14 days of postharvest cold storage showed a progressive increase in the number of differentially expressed genes (DEGs) in both cultivars. More (1264) DEGs were identified in ‘Big Top’ compared to ‘Sagittaria’ (746 DEGs). Both cultivars showed a downregulation of pathways related to photosynthesis, and an upregulation of pathways related to amino sugars, nucleotide sugar metabolism and plant hormone signal transduction with ethylene pathways being most affected. Expression patterns of ethylene related genes (including biosynthesis, signaling and ERF transcription factors) correlated with genes involved in cell wall modification, membrane composition, pathogen and stress response, which are all involved in development of chilling injury. Overall, the results show that common pathways are activated in the fruit of ‘Big Top’ nectarine and ‘Sagittaria’ peach in response to cold storage but clear differences within these pathways characterize cultivar-specific responses.